2012
DOI: 10.1128/jvi.01574-12
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome of Staphylococcus aureus Phage SA11

Abstract: A novel lytic bacteriophage, SA11, infecting Staphylococcus aureus was isolated, and the whole genome was sequenced. It belongs to the siphoviridae based on electron microscopic observation. It has a linear double-stranded DNA genome of 136,326 bp. Genomic analysis showed that it is distantly related to Staphylococcus phages A5W, K, ISP, Sb-1, and G1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 11 publications
(8 reference statements)
0
18
0
Order By: Relevance
“…These dimensions correspond to those of other twortlikeviruses infecting S. aureus (5). Consequently, phage SA11, closely related to Romulus and Remus, was presumably erroneously described as a siphovirus (14).…”
Section: Isolation and Morphologymentioning
confidence: 99%
See 1 more Smart Citation
“…These dimensions correspond to those of other twortlikeviruses infecting S. aureus (5). Consequently, phage SA11, closely related to Romulus and Remus, was presumably erroneously described as a siphovirus (14).…”
Section: Isolation and Morphologymentioning
confidence: 99%
“…This genus includes staphylococcal phages K (7), G1, Twort (8), Sb-1 (9), ISP (10,11), A5-W, Staph1N, Fi200W, P4W, 676Z, A3R, MSA6 (12,13), SA11 (14), and GH15 (15). Their double-stranded genomes contain 127,188 bp to 140,194 bp, display a GϩC content of 30.04 to 30.60%, and contain 183 to 217 open reading frames (ORFs).…”
mentioning
confidence: 99%
“…The results showed that the Staphylococcus phages K, G1, Twort, A5W, Sb-1, ISP, SA5, GH15, JD007, SA11, vB_SauM_Remus, vB_SauM_Romulus, S25-3, S25-4, phiIPLA-RODI, phiIPLA-C1C, phiSA012, Team1, P108, MCE-2014, 812, and SA1 belong to the Myoviridae family and are all lytic phages789101112131415. The previous report shows that phage phiIPLA-RODI and phiIPLA-C1C are lytic phages11, our results were consistent with the studies reported previously.…”
Section: Resultsmentioning
confidence: 99%
“…Published data show that they have a wide host range and can potentially be used for phage therapy. To date, the complete genome sequences of dozens of Staphylococcus phages of the Myoviridae family have become available, including phage K, G1, Twort, A5W, Sb-1, ISP, SA5, GH15, JD007, SA11, vB_SauM_Remus, vB_SauM_Romulus, S25-3, S25-4, phiIPLA-RODI, phiIPLA-C1C, phiSA012, Team1, P108, MCE-2014, 812, SA1, Staphy1N, MSA6, 676Z, P4W, and Fi200w789101112131415. These phages can potentially be used for the treatment of infectious diseases caused by Staphylococcus aureus in animal models.…”
mentioning
confidence: 99%
“…As shown, phage genetics vary among phages of different hosts, even in an interlinked supply chain like the industry of food processing [24][25][26][27][28][29]. The main bottleneck for functional overall genomics, including phage genomics, is the low number of available genomes and described genes (open reading frames or ORFs).…”
Section: Phage Genome Sequencing Focusing On Economic Applications Inmentioning
confidence: 99%